Essential role of YopD in inhibition of the respiratory burst of macrophages by Yersinia enterocolitica. - Hartland, E L (1994)
The respiratory burst is a key element of the bactericidal armamentarium of phagocytes. In this study we have shown that a virulent strain of Yersinia enterocolitica serogroup O:9 completely inhibited the ability of murine bone marrow-derived macrophages to mount a respiratory burst in response to stimulation by zymosan. This property of the bacterium was abrogated by curing the strain of its 71.5-kb virulence plasmid and by transposon mutagenesis of the plasmid-borne yopD gene. Derivatives of the bacterium which were unable to inhibit the respiratory burst were also less able to disrupt cytoskeletal actin and to resist phagocytosis. yopD mutants also showed an impaired ability to dephosphorylate phosphotyrosine residues in macrophage proteins and were completely avirulent for mice. All of these defects were fully or partly restored by trans-complementation of a yopD mutant with a cloned yopD gene. The results of this study and those of previous work with YopD (R. Rosqvist, A. Forsberg, and H. Wolf-Watz, Infect. Immun. 59:4562-4569, 1991) suggest that YopD functions chiefly by facilitating the transport of virulence plasmid-encoded proteins, such as YopE, a cytotoxin, and YopH, a protein tyrosine phosphatase, across the cytoplasmic membrane to their targets within host cells. The combined action of these Yops on cytoplasmic proteins, especially actin, could explain the effects of virulent Y. enterocolitica on macrophage morphology, phagocytic capacity, and respiratory burst activity, all of which rely on cytoskeletal integrity to function normally.